CLOSE ENCOUNTERS: CREATING A SAFE SPACE FOR INTERCULTURAL BIBLE READING - Van der Walt, Charlene (Scriptura, 2012)
Theoretically the process of intercultural Bible reading should create a safe space where the voice of the individual can be heard in community with others. It should be a space where the individual is not only free to speak but also to have the innate experience of truly being heard. In this respect the intercultural Bible reading experience becomes a space that promotes human dignity and has the inherent capacity to facilitate social transformation. Although these Bible study groups can ideally be a safe space with the potential for social transformation, the practical reality shows a more complicated dynamic. Two important factors that contribute to the complexity are the ideological framework of individual participants and the underlying power dynamic in the social interaction. To bring the concepts of power and ideology in intercultural Bible reading into focus, an empirical study was conducted. My two part paper will discuss this qualitative research project that took place in Grahamstown in the Eastern Cape province of South Africa. In the culturally diverse study, groups of women engaged with one another in a discussion of the biblical text in 2 Samuel 13:1-22 which describes the rape of Tamar. Part I of my contribution functions as the theoretical backbone to the empirical exploration that will be discussed in Part II.